Lexicography and Terminology : a Worldwide Outlook. - Karpova, Olga (Cambridge Scholars Pub., 2009)
The present book contains a collection of works devoted to current trends in theoretical and practical lexicography, terminology and terminography. All papers are divided into two main sections. Part I: Lexicography deals with analysis of historical and typological problems in lexicography with special reference to English, Italian, Russian and Southern African dictionaries for general- and special- purposes. The main focus is given to the description of principles in lexicographic presentati ...